Anomalous detwinning in constrained Cu nanoparticles. Issue 27 (7th July 2020) - Ge, Mengke; Yuan, Wenjuan; Wang, Kai; He, Jia; Xi, Wei; Luo, Jun
Abstract : The detwinning process in a 9 nm graphene-constrained Cu nanoparticle was investigated at 1009 °C via in situ HRTEM. Instead of the expected reverse glide of the twinning dislocations, two new twins were formed; the four twin zones rotated synergistically before vanishing. Abstract : In this work, the detwinning process in a 9 nm graphene-constrained Cu nanoparticle was investigated at 1009 °C via in situ high-resolution transmission electron microscopy. Instead of the expected reverse glide of the twinning dislocations, two new twins were formed; the four twin zones rotated synergistically before vanishing. Furthermore, the twin boundary migration energy and the system energy were increased continuously with detwinning. The increased resistance to twin boundary migration in constrained nanoparticles enriches our understanding of the twinning mechanism and may facilitate the design of high-strength and high-ductility nanomaterials.